2010
DOI: 10.1111/j.1600-079x.2010.00791.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and celecoxib improve the outcomes in hamsters with experimental pancreatic cancer

Abstract: Pancreatic cancer is a major health problem because of the aggressiveness of the disease and the lack of effective systemic therapies. Melatonin (MEL) has antioxidant activity and prevents experimental genotoxicity. The specific inhibitor of cyclooxygenase-2 (COX-2), celecoxib (CEL), increases the efficacy of chemoradiotherapy in advanced pancreatic cancer. The objective of the study was the comparison and synergic effect of MEL and CEL during either the induction or progression phases of the tumor process, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…The ability of melatonin to inhibit the growth of several tumor cell lines has been repeatedly observed (Leja-Szpak et al, 2010;Jung-Hynes et al, 2010;Padillo et al, 2010;Park et al, 2010). A growing body of evidence implicates melatonin's antioxidant actions in the inhibition of cancer development and growth (Mediavilla et al, 2010).…”
Section: Cancermentioning
confidence: 98%
“…The ability of melatonin to inhibit the growth of several tumor cell lines has been repeatedly observed (Leja-Szpak et al, 2010;Jung-Hynes et al, 2010;Padillo et al, 2010;Park et al, 2010). A growing body of evidence implicates melatonin's antioxidant actions in the inhibition of cancer development and growth (Mediavilla et al, 2010).…”
Section: Cancermentioning
confidence: 98%
“…Melatonin-dependent growth inhibition of rat hepatoma 7288CTC cells was associated with reduced cAMP levels and, presumably, to reduced phosphorylation of ERK2, a downstream target of 13-HODE [101]. Given that ERK activation is involved in phosphorylating MDM2 [102] and FoxO3a [103], two key apoptotic factors that have been demonstrated to be reduced in their phosphorylated form after melatonin administration [28,104], it could be argued that melatonin exerts a relevant apoptotic effect through a 13-HODE-dependent downregulation of ERK phosphorylation.…”
Section: Melatonin In Gastrointestinal and Colon Cancersmentioning
confidence: 99%
“…A number of studies have examined the role of melatonin in influencing the growth of experimental pancreatic cancers [104,[107][108][109] and several have evaluated the role of induced apoptosis as a means by which melatonin reduced their growth. Leja-Szpak and co-workers [107] found that melatonin had pro-apoptotic actions on a commonly investigated human pancreatic carcinoma, PANC-1 cells.…”
Section: Melatonin In Gastrointestinal and Colon Cancersmentioning
confidence: 99%
“…High concentrations of MEL (more than 100 μM) enhance the effect of chemotherapeutic drugs, both in cultured cancer cells [1419] and in vivo [20,21], suggesting that in particular conditions MEL can be harmful, if not deleterious, for cancer cells.…”
Section: Introductionmentioning
confidence: 99%